Acute intestinal obstruction due to gastrointestinal stromal tumours: case report - Newme, Kewithinwangbo; Khongwar, Donkupar; Hajong, Ranendra; Raphel, Vandana (International Surgery Journal, 2020)
Gastrointestinal stromal tumours (GIST) as such is a rare disease, but according to some study it may end up to malignant type in approximately 10-30%. Herein we present a 2 cases of GIST who presented with acute intestinal obstruction in emergency department. In imaging studies (X-ray erect abdomen, ultrasonography abdomen), it showed a features of intestinal obstruction but could not rule out the exact mechanism or pathology behind the obstruction. As commonly adhesions is a main culprit behind the cause of acute intestinal obstruction in case of any post-operative patient. So, we try to highlight that in case of any old aged individual and in virgin abdomen GIST should be keep in mind as a cause of intestinal obstruction.